Answer:
3*10^5 or 300,000 cant remember witch one it is
Step-by-step explanation:
1.5*10^2= 150
2*10^3=2,000
150*2000=300,000
3*10^5
Answer:
<u></u>
- <u>She should aim 6 feet down the wall</u>
Explanation:
The diagram attached sketches the situtation.
Since the angle with which the ball hits the wall is the same with which it bounces, angle β is the same for the two shown triangles.
Then, since both are right triangles, then all the angles are congruent and the triangles are similar. Hence, you can equal the ratios of the sides, to make an equation:
You have other equation:
Substitute
- 2y + y = 18
- 3y = 18
- y = 18/3
- y = 6 ← this is the distance down the wall where the ball should hit
Then, she should aim 6 feet down the wall.
Let's do this by Briot-Ruffini
First: Find the monomial root
x - 2 = 0
x = 2
Second: Allign this root with all the other coeficients from equation
Equation = -3x³ - 2x² - x - 2
Coeficients = -3, -2, -1, -2
2 | -3 -2 -1 -2
Copy the first coeficient
2 | -3 -2 -1 -2
-3
Multiply him by the root and sum with the next coeficient
2.(-3) = -6
-6 + (-2) = -8
2 | -3 -2 -1 -2
-3 -8
Do the same
2.(-8) = -16
-16 + (-1) = -17
2 | -3 -2 -1 -2
-3 -8 -17
The same,
2.(-17) = -34
-34 + (-2) = -36
2 | -3 -2 -1 -2
-3 -8 -17 -36
Now you just need to put the "x" after all these numbers with one exponent less, see
2 | -3x³ - 2x² - 1x - 2
-3x² - 8x - 17 -36
You may be asking what exponent -36 should be, and I say:
None or the monomial. He's like the rest of this division, so you can say:
(-3x³ - 2x² - x - 2)/(x - 2) = -3x² - 8x - 17 with rest -36 or you can say:
(-3x³ - 2x² - x - 2)/(x - 2) = -3x² - 8x - 17 - 36/(x - 2)
Just divide the rest by the monomial.
Step-by-step explanation:
![M=\left[\begin{array}{ccc}1&-1/f_2\\0&1\end{array}\right] \left[\begin{array}{ccc}1&0\\d&0\end{array}\right] \left[\begin{array}{ccc}1&-1/f_1\\0&1\end{array}\right]\\=\left[\begin{array}{ccc}1&-1/f_2\\0&1\end{array}\right]\left[\begin{array}{ccc}1&-1/f_1\\d&-d/f_1\end{array}\right]\\=\left[\begin{array}{ccc}1-d/f_2&-1/f_1+d/f_1f_2\\d&-d/f_1\end{array}\right]\\\\|M|=[-d/f_1+d^2/f_1f_2]-[-d/f_1+d^2/f_1f_2]=0\\\\-1/f=M_{12}=-1/f_1+d/f_1f_2\\1/f=M_{12}=+1/f_1-d/f_1f_2\\](https://tex.z-dn.net/?f=M%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%26-1%2Ff_2%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%260%5C%5Cd%260%5Cend%7Barray%7D%5Cright%5D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%26-1%2Ff_1%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%5C%5C%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%26-1%2Ff_2%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%26-1%2Ff_1%5C%5Cd%26-d%2Ff_1%5Cend%7Barray%7D%5Cright%5D%5C%5C%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1-d%2Ff_2%26-1%2Ff_1%2Bd%2Ff_1f_2%5C%5Cd%26-d%2Ff_1%5Cend%7Barray%7D%5Cright%5D%5C%5C%5C%5C%7CM%7C%3D%5B-d%2Ff_1%2Bd%5E2%2Ff_1f_2%5D-%5B-d%2Ff_1%2Bd%5E2%2Ff_1f_2%5D%3D0%5C%5C%5C%5C-1%2Ff%3DM_%7B12%7D%3D-1%2Ff_1%2Bd%2Ff_1f_2%5C%5C1%2Ff%3DM_%7B12%7D%3D%2B1%2Ff_1-d%2Ff_1f_2%5C%5C)